Risky disciplining: on interdisciplinarity between sociology and cognitive neuroscience in the governing of morality - Wade, Matthew (2022)
The neuroscience of morality presents novel approaches in exploring the cognitive and affective underpinnings of moral conduct, and is steadily accumulating influence within discursive frames of biocitizenship. Many claims are infused with varieties of neuro-actuarialism in governing morally risky subjects, with implications that other fields should observe closely. Sociologists and other social scientists, however, have typically been reluctant to interject their expertise. However, a resurgent sociology of morality offers the means by which closer engagement may be realized. In encouraging this interdisciplinarity, a brief outline of recent developments in the neuroscience of morality is provided. Some interdisciplinary collaborations are then explored, which weave together novel methodological affordances from the neurosciences with conceptual models from sociological inquiry. A brief overview of ‘neuroliberalism’ follows, to concretize the growing appeal and practical application of the psy- and neurosciences in governing moral conduct. Finally, some tentative ‘provocations’ are offered, towards fostering moralities that, ultimately, we can live with.